Enhancing the Assessment of Coercive Control in Spanish Femicide Cases: A Nationally Representative Qualitative Analysis - Viñas-Racionero, Rosa (Journal of family violence, 2025)
PurposeCoercive control is a power dynamic central to intimate partner violence (IPV) and consists of tactics to limit one’s partner’s autonomy through constraint, regulation of everyday life, isolation, pursuit, and intimidation and physical force. Such tactics may potentially signal a risk for future lethal or near lethal violence; hence, proper evaluation may enhance the utility of clinical femicide risk assessments. The goal of this study is to explore coercive control behaviors preceding partner femicides in Spain with the intention to provide guidance for its assessment by first responders and law enforcement.MethodsResearchers from the Department of State for Security of the Ministry of Interior collected a nationally representative sample of 150 femicides (2006–2016). Qualitative data included 958 semi-structured interviews with victims and offenders’ social networks, which provided information about relationship dynamics leading up to the murders. Additionally, 225 interviews with law enforcement and occasionally offenders were used to corroborate and contextualize victim and offender social networks.ResultsQualitative analysis indicated four indicators of coercive control (i.e., microregulation and restriction, victim isolation, surveillance and pursuit, and physical violence), which were present in 85% of the cases. While these indicators were commonly present, their manifestation varied based on relationship history and victims’ responses.ConclusionThe findings suggest that incorporating coercive control indicia into clinical femicide risk assessments is useful and may enhance their accuracy.